The relationship between spiritual well-being and fear of COVID-19 among Turkish elders - Durmuş, Mustafa (Journal of religion, spirituality & aging, 2022)
The aim of this research is to determine the relationship between spiritual well-being levels and coronavirus fear levels of individuals over 65 years old during the COVID-19 outbreak. The study adopted a cross-sectional and corelational design. The research was conducted between July 1–30 in the city of Muş in Turkey’s Eastern Anatolia Region. The universe of the study consisted of 1780 individuals over 65 years old enrolled in a family practice center located in the city center between the specified dates. Personal information form, Spiritual Well-being Scale (FACIT-Sp) and Coronavirus Phobia Scale (C19P-S) were used to collect data. Data coding and analysis were performed in the computer environment with SPSS 25 package program. Analysis of data used number, mean, percentage distribution and Pearson correlation analysis. Participants had mean total points for the spiritual well-being scale of 28.61 ± 5.54, with mean coronavirus fear points of 59.66 ± 15.40. There was a moderate level correlation between spiritual well-being and coronavirus fear in individuals, with meaning and belief levels above the mean. Individuals with chronic disease had psychological fear levels above the mean, with somatic, economic and social fear levels below the mean. A significant negative relationship was found not only between the spiritual meaning sub-dimension and individuals’ fear of coronavirus but also between the peace sub-dimension and their fear of coronavirus. The data show that as individuals’ spirituality increases, their fear of coronavirus levels decrease.